The Effects of Language Background and Parental Education on Measures of Cognitive Ability: An Analysis of the WPPSI-IV Cognitive Profiles of Monolingual, Simultaneous Bilingual, and Sequential Bilingual German Children Aged 4 to 7 Years - Franziska Walter; Monika Daseking; Franz Pauls (MDPI AG, 2024)
Background: The present study investigated the possible effects of language background (monolinguals, simultaneous bilinguals, and sequential bilinguals) and parental education (no/low, medium, high, and highest parental education) on measures of cognitive ability provided by the Wechsler Primary and Preschool Scale-Fourth Edition (WPPSI-IV). Methods: Statistical analyses were based on a sample of 290 children (130 females, 160 males). Three multivariate variance analyses were conducted to identify possible effects. In cases of statistically significant main effects, post hoc analyses were additionally performed to identify group differences. Results: The results indicated that simultaneous bilinguals performed more similarly to monolinguals than sequential bilinguals. On average, sequential bilinguals achieved significantly lower scores on the Verbal Comprehension Index (VCI), the Vocabulary Acquisition Index (VAI), and the associated subtests than monolinguals and simultaneous bilinguals. Significantly lower average scores on VAI and the associated subtests were found for simultaneous bilinguals compared to monolinguals. Children with parents having no, a lower, or a medium educational level achieved significantly lower scores on VCI, VAI, and the FSIQ than children with parents having a high or highest educational level on average. Conclusions: The present findings suggest that the WPPSI-IV represents a suitable and reliable test battery for the assessment of cognitive skills in children with different language backgrounds and parental educational levels.